Keadilan Restoratif sebagai Solusi Alternatif Penanganan Tindak Pidana di Era Digital - Arianto, Rafi Fadhlurrohman; Prasetyo, Boedi (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to analyze the application of restorative justice as an alternative solution in handling criminal offenses in the digital era, which is marked by increasingly complex forms of crime and their impact on victims. The contribution of this research lies in its effort to offer a more humanistic, participatory, and relevant approach to punishment in line with the dynamics of modern criminal law, particularly in addressing legal challenges in digital spaces. The methodology used is library research with a qualitative approach and normative legal study, by analyzing statutory regulations, legal theories, and related scholarly literature. The findings indicate that restorative justice can serve as an effective alternative to conventional sentencing for resolving digital-based criminal offenses, as it promotes peaceful resolution between offender and victim, restores social relations, and reduces the burden on the formal criminal justice system. However, the implementation of restorative justice still faces challenges such as low digital legal literacy, unprepared infrastructure, and the absence of standardized procedural guidelines.